Tuning the solid-state fluorescence of chalcone crystals via molecular coplanarity and J-aggregate formation. Issue 14 (26th January 2017) - Yu, Fangfang; Wang, Mingliang; Sun, Hao; Shan, Yaqi; Du, Man; Khan, Arshad; Usman, Rabia; Zhang, Wei; Shan, Hongbin; Xu, Chunxiang
Abstract : Eleven crystals of chalcone were obtained. Polymorphism and their solid-state fluorescent properties mainly affected by molecular coplanarity and J-aggregate formation are investigated. Abstract : Four chalcones bearing the 1, 3-diarylpropenone moiety 3-(9-anthryl)-1-(4-chloro)prop-2-en-1-one (I ), 3-(1-pyrenyl)-1-(4-chlorophenyl)prop-2-en-1-one (II ), 1-phenyl-3-(1-pyrenyl)prop-2-en-1-one (III ) and 3-(1-pyrenyl)-1-(4-nitrophenyl)prop-2-en-1-one (IV ) were synthesized and different crystal forms were obtained from different solvents by slow evaporation includingI (Ia, Ib ), II (IIa, IIb, IIc ), III (IIIa, IIIb, IIIc, IIId ) andIV (IVa, IVb ). Their structures and optical properties were characterized by single crystal X-ray diffraction (SCXRD), powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), UV-Vis absorption spectroscopy and fluorescence spectroscopy. Hirshfeld surface calculations were also used for intermolecular interaction analysis. It has been found that polymorphism and conformational isomorphism exist in these crystals.Ib andIIIa adopt a cis configuration with respect to the central CC bond while the other forms exhibit a trans configuration, except for those without single crystal X-ray analysis. BothIb andIIb have two crystallographically independent molecules in their asymmetrical unit which has not been found in reported chalcone crystals. Those crystals with a cis configuration show a higher melting point and no fluorescence. Crystals with a trans configuration are fluorescent and their emission wavelengths are mainly effected by the torsion extent of the molecules and J-aggregate formation.